PENGARUH KEBIJAKAN FISKAL TERHADAP DEFISIT APBN DI INDONESIA TAHUN 2007-2022 - Magadhendra, Foggi; Soebagyo, Daryono; Indira Hasmarini, Maulidyah (LP2M Universitas Bina Bangsa, 2025)
The State Revenue and Expenditure Budget (APBN) is an annual financial plan approved by the House of Representatives that includes state revenue and state expenditure in the same year. This study was conducted to determine the influence of fiscal policy, in this case investment, economic growth, and taxes on the state budget deficit for the 2007-2022 period. The type of data used is time series data with a sequence of time. Classical assumption tests such as Ramsey Reset, Multicollinearity, Normality, Heteroscedasticity, and Autocorrelation tests were used in this study. The results of the study show that economic growth has a negative effect on the state budget deficit and taxes have a positive effect on the state budget deficit. Meanwhile, investment has a positive value, but it has not been able to simultaneously affect the state budget deficit for the 2007-2022 period. The state budget deficit must always be controlled in line with domestic economic growth, because if the state budget continues to experience a deficit, the government will be increasingly unable to meet domestic needs.